Determinants of adherence in patients on ART on the Copper Belt Province in Zambia - Chisa, Sume Percival (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.